Perbaikan Kualitas Hidup Pasien Diabetes Melitus Tipe 2 di RSUD Dr. H. Moch. Ansari Saleh Banjarmasin Dengan Intervensi Brief Counseling - Muhammad Reza Pahlevi; Abdul Rahem; Valentina Metasartika (Jurnal Ilmiah Manuntung, 2018)
The study about the effect of brief counseling on quality of life of diabetes mellitus patients were conducted at RSUD Dr. H. Moch. Ansari Saleh Banjarmasin. This study using a randomized controlled trial design. Subjects who met the inclusion criteria were 156 patients randomly into two groups, 78 patients who received the intervention and 78 patients did not receive the intervention. Exclusion criteria were pregnancy patients, deaf, illiterate and uncooperative. The data collected by questionnaires Euro-Qol EQ-5D. The quality of life data were analyzed by multivariate statistic test. The result showed that the quality of life scores in the control group and the intervention group were both significantly increased with p <0.05. Multivariate analysis both group at pre and median study were significant different, while at the post study was not significant different. There were improving quality of life of patients with diabetes mellitus who received the brief counseling is greater than patients who did not receive the intervention